Socio-economic assessment of drought impacts in Lesotho: implications for early action - Relebohile Agnes Mojaki; Makoala Vitalis Marake; Evan Easton-Calabria; Joalane Rethabile Marunye; Erin Coughlan de Perez (International Journal of Climate Change Strategies and Management)
Purpose – Lesotho is one of the most vulnerable countries to effects of climate change with resultant recurrent drought. Drought and dry spells have become a common feature that causes crop failure which subsequently causes food insecurity for agrarian communities. While drought-related research has explored the association between rainfall and crop production, there is a gap in understanding people’s experiences of drought impacts and their opinion about what actions could be taken to avoid such impacts in the future. This study aims to ask: what are people’s experiences of drought and potential early actions that could save livelihoods and reduce human suffering? Design/methodology/approach – A qualitative research approach was adopted where this paper carried out consultations in three agroecological zones, i.e. Southern Lowlands, Northern Lowlands and Mountains of Lesotho. Overall, this paper conducted 48 community consultations where genderized focus group discussions (mixed elderly, mixed youth, middled aged men and women) and nine key informants (local authorities, schoolteachers, wisemen and women in the community) interviews were conducted. Furthermore, interviews with stakeholders at the district level (sectoral leaders in disaster risk reduction sub-sectors) were conducted. Findings – This study finds that there are interlinked socio-economic, productive and environmental impacts. Drought-related impacts reported were: cost of food, prevalence of diarrhoea in children under five years of age, conflicts over resources, animal diseases and mortality, aridity and crop failure. Informants also perceived the following actions could be taken before a drought is manifested: clear agro-climatological early warning messages, tailor-made drought-relevant advisories, water harvesting and availability of drought-tolerant seeds. It is thus imperative to streamline policy interventions regarding dissemination of early warning messages and anticipatory actions to reduce the negative impacts of drought on livelihoods. Research limitations/implications – In any qualitative study, the researchers need to reflect on their positionality and how that may influence the research process, outcomes and the general limitations of the research methods (Quandt, 2021). Given that the research team has worked with humanitarian organisations in the study area after which development interventions were implemented, this might have led to interviewees exaggerating the negative impacts of drought hoping the team to bring assistance into the community. In contrast, others may have downplayed the impact and anticipatory actions they deem necessary because of concern that people from different institutions come to ask questions without feedback. Practical implications – This study provides much-needed evidence on how communities affected by drought conceptualise it and how it affects their livelihoods. It delivers an understanding of the nature of the impacts of drought and the nature of anticipatory actions perceived as essential in reducing these impacts and, in so doing, seeks to inform policymakers on designing interventions informed by evidence on lived experience. Future humanitarian and policy interventions to prepare for droughts can use this evidence to identify the type of support that would be the most well-received by community members who are preparing for long-term drying trends in their region. Originality/value – The study presents an understanding of people’s opinions of the nature and state of drought impacts, which are key to any effort towards developing and implementing relevant anticipatory action interventions to minimise the impacts of drought.